Introduction of a modified analgesic ladder in the emergency department: Effect on oxycodone use for back pain - Ly, BPharm, GradCertPharmPrac, Jenny; Roman, BPharm (Hons), MPP, Cristina P.; Luckhoff, MB, ChB, FACEM, Carl; Cameron, MBBS, MD, FACEM, FCEM (Hon), Peter A.; BPharm, GradDipHospPharm, PhD, AdvPracPharm, FSHP, FISOPP, Michael J.; Mitra, MBBS, MHSM, PhD, FACEM, Biswadev (Journal of Opioid Management, 2021)
Objective: The aim of this study was to assess the introduction of an analgesic ladder and targeted education on oxycodone use for patients presenting to the emergency department (ED). Design: A retrospective pre-post implementation study was conducted. Data were extracted for patients presenting from June to July 2016 (preintervention) and June to July 2017 (post-intervention). Setting: The EDs of a major metropolitan health service and an affiliated community-based hospital. Participants: Patients with back pain where nonpharmacological interventions such as mobilization and physiotherapy are recommended as the mainstay of treatment. Interventions: A modified analgesic ladder introduced in May 2017. The ladder promoted the use of simple analgesics such as paracetamol and nonsteroidal anti-inflammatory drug (NSAIDs) prior to opioids and tramadol in preference to oxycodone in selected patients. Main outcome measure(s): The proportion of patients prescribed oxycodone and total doses administered. Results: There were 107 patients pre and 107 post-intervention included in this study. After implementation of the analgesic ladder, 78 (72.9 percent) preintervention patients and 55 (51.4 percent) post-intervention patients received oxycodone in ED (p = 0.001). The median oxycodone doses administered in the ED was 14 mg (interquartile range: 5-20 mg) and 5 mg (interquartile range: 5-10 mg; p < 0.001), respectively. On discharge from hospital, a prescription for oxycodone was issued for 36 (33.6 percent) patients preintervention and 26 (24.3 percent) patients post-intervention (p = 0.13). Conclusions: Among patients with back pain, implementation of a modified analgesic ladder was associated with a statistically significant but modest reduction in oxycodone prescription. Consideration of multifaceted interventions to produce major and sustained changes in opioid prescribing is required.